Pore-Size Distribution Evolution of Intact, Compacted, and Saturated Loess from China during Consolidation and Shearing - Ping Li; Shengjun Shao; Tao Xiao; Dandan Zhu (Advances in Civil Engineering)
To examine the pore-size distribution (PSD) evolution of intact, compacted, and saturated loess during deformation associated with consolidation or shearing, nominally identical specimens were consolidated to different confining stresses or sheared to sequential axial strains under the same confining stress, and the PSD of each deformed specimen was characterized using the Mercury intrusion porosimetry (MIP) technique. The results show that the PSD evolution during consolidation is similar to that during shearing, suggesting that the PSD evolution depends mainly on whether the soil volume contracts or expands. The volumetric contraction results mainly from compression of interaggregate pores, and the intra-aggregate PSD or intra-aggregate pores are not affected. In compacted and saturated loess, interaggregate pores are compressed from the larger to the smaller, while in intact loess, the PSD evolution depends on whether the soil yields. This difference arises from different cementations that dominate particle associating in three soils. In intact loess, carbonate cementations that can be damaged by remolding and loading contribute greatly to particle associating. As a result, the stability of a pore is controlled not only by its size but also by carbonate cementations at surrounding particle contacts. Clay cementations that play the dominant role in particle aggregating in compacted loess are resistant to loading; thus, aggregates could not be destroyed by loading and the mechanical responses of compacted loess are in fact interactions among aggregates. Both carbonate and clay cementations can fail under the combined effect of loading and inundation, leading to disintegration of aggregates and turning of the loess structure from the double-structured to the uniform type.